Arranjos familiares, apoio social e fragilidade em idosos da comunidade - Mota, Gabriela Marques Pereira (2021)
The family is considered the main assistance, interaction and support network in old age. However, the effectiveness of this protective factor is not always observed. It is known that with advancing age, the chances of developing diseases and dependence increase, intensifying the needs for support and care. Social safety nets play an important role in maintaining family and community ties, contributing to the health and well-being of the elderly. This study aims to analyze a constitution of family arrangements of elderly people registered in a Reference Center for Social Assistance and its relationship with social support, fragility, quality of life and cognition, considering two moments of data collected in the period from 2012 to 2019. In addition to analyzing, from the perspective of the elderly, possible tensions in the family context. This is a longitudinal study using mixed methods with concomitant triangulation that continued the research carried out between 2012 and 2016 with 247 elderly people. Data collection occurred through a home visit with an approximate time of one hour. Instruments were used to obtain sociodemographic data, Edmonton's Fragility Scale to identify frailty; The Montreal Cognitive Assessment for screening cognitive impairment, quality of life (Whoqol-bref and the old), building a Genogram and Ecomapa to assess family and social relationships through tapes. Quantitative data were analyzed using descriptive statistics and the Wilcoxon and Mann Whitney comparison test, those with a qualitative approach using content analysis based on Bardin, using dialectical materialism as the theoretical framework, and Agnes Heller's concept of daily life. 84 elderly people participated in this study. It was noticed that the majority remained living with a family member (73.8%), 54.7% increased their relations with the community. The fragility and non-statistical cognition related to the type of arrangement, however, elderly people who lived alone had worse quality of life in the physical (p0.044) and psychological domains (p0.031) and better scores in relation to the total Whoqol-old ( p0.036). Elderly people who lived with young grandchildren worsened in the social relationship (p0.047) and Whoqol-bref (p0.029) domains, and improved in death and dying (p <0.001) and Whoqol-old (p0, 019). Living with a spouse only worsened the functioning of the sensory abilities (p0.022) and improvements in the domain death and dying (p0.028). Through the categories “Relational processes of the elderly with the family”, “Changes in the elderly's family configuration”, “Support and social support offered and received”, it was observed that family arrangements are dynamic, sources of tensions, conflicts and relationships of interdependence. It is concluded that regardless of the type of family arrangement, the relationships built between its members are essential for the provision of support and support in old age, interfering in their health conditions. It is urgent to reformulate public policies aimed at this specific population in order to provide quality services to this social segment that is growing.